A SECURE HYBRID AUTHENTICATION SYSTEM (Global Journal of Advanced Engineering Technologies and Sciences, 2022)
Numerous shoulder surfing techniques have been developed, however predictable secret word patterns are now vulnerable to dictionary assaults, eve dropping, and shoulder surfing. At the same time, text passwords are the most often utilised authentication publicising strategy. In previous years, there were some graphical password schemes that were intended. The majority of We have suggested word-based graphical password schemes since users prefer word-based passwords over pure graphical ones. Unfortunately, no hybrid digital graphical password system is created by any of the current approaches. In this study, we propose an enhanced graphical password that is primarily text-based, numerical-based, shoulder surfing resistant, and also employs additional techniques such as social engineering resistance, eves dropping, and dictionary attack resistance through the use of colours. The operator can observe the proposed system's security, usability, and resilience to different threats by logging in to the system in a reliable, easy, and efficient manner.